Analisis Pusat Pendidikan dan Pelatihan Olahraga untuk Siswa: Sistem Manajemen - Mikhael Septiano; Aziz Amrulloh (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. of the study is to provide a breeding ground for student athletes. This institution not only provides institutional facilities, but also implements a management system that covers aspects of strategic planning, resource organization, implementation of institutional programs, as well as periodic monitoring and evaluation. The purpose of this study is to analyze the management system of sports education and training center for students (BPPLOP) Central Java, based on direct experience in the field and an in-depth scientific approach. Materials and methods the type of research used in this study is qualitative research. The population in this study includes all individuals directly involved in the management and coaching of student athletes at BPPLOP Central Java. In this study, the instruments used include questionnaires, observation sheets, and documentation. The data analysis technique in this study used a quantitative descriptive approach with the help of a Likert scale. Results In terms of planning, sport education and training center for students Central Java obtained an average score of 79%, while organizing received the highest score of 80%. In terms of execution, the average score was 76%, and in terms of control, the average score was 78%. Conclusion This study found that Central Java BPPLOP management system has been implemented well based on the data results show that 70% of the population in BPPLOP agree with the statements from the questionnaire in the new findings. Future study is expected to analyze and evaluate the programs that have been carried out over the past five years and the advantages of the programs that have been carried out.